Multidisciplinary osteoporosis management of post low‐energy trauma hip‐fracture patients. Issue 1 (31st December 2012) - Skorupski, Nicole; Alexander, Ivy M.
Abstract: Purpose: The purpose of this article is to increase awareness of osteoporosis incidence in patients with hip fracture among providers and allied health professionals, to increase osteoporosis recognition and treatment in post hip‐fracture patients, and to provide guidance on how to improve continuity of care and collaboration between members of the multidisciplinary healthcare team. Data sources: Recent evidence from the literature is reviewed to identify effective management strategies for post low‐energy trauma hip‐fracture patients and prevention of future osteoporotic fracture, regardless of osteoporosis diagnosis prior to the initial fracture. Conclusions: Despite the availability of accurate screening technologies and highly efficacious antiosteoporosis medications, implementation of these measures for low‐energy trauma hip‐fracture patients remains critically low. This is because of a number of factors including hesitancy to integrate care across specialty lines, lack of reliable referral systems, and resistance to change. There is also a lack of recognition of the connection between low‐energy trauma hip fracture and osteoporosis by many healthcare professionals. Implications for practice: All members of the multidisciplinary care team are called to action to adopt osteoporosis evaluation and treatment strategies that research has shown to be effective on a larger scale in the post hip‐fracture setting.